Performance of elite genotypes of barley, chickpea, lentil, and wheat under conservation agriculture in Mediterranean rainfed conditions. (April 2021) - Devkota, Mina; Patil, S. B.; Kumar, Shiv; Kehel, Zakaria; Wery, Jacques
Abstract: Conservation agriculture (CA) practices are becoming more important in Mediterranean rainfed areas due to their potential to minimize climatic risk, reduce soil erosion, and improve soil quality and water availability. Due to minimum soil disturbance and crop residue retention, the soil environment for crop growth and development can differ between CA and conventional tillage (CT) practice. However, breeding targets for improving yield performance in CA system remain poorly explored. The objective of this study was to assess the performance of elite genotypes of barley, chickpea, lentil, and wheat grown under CA, a promising alternative agricultural practice in the Mediterranean rainfed conditions. A three-year field study, with contrasting rainfall pattern, was conducted in the International Center for Agriculture Research in the Dry Areas's research field in Morocco to evaluate the tillage × genotype interaction and its consequence for yield performance of barley, chickpea, lentil, and wheat. Thirteen elite genotypes for each crop were planted under both CA and CT systems. Wheat and chickpea produced significantly higher grain yield (+62% for wheat and +43% for chickpea) under CA than in CT, while lentil and barley performed equally under both systems. Significant effect of tillage × genotype was more frequent for chickpea and wheat than for barley and lentil. Increased yield under CA, mainly in dry year, was associated with higher harvest index (HI). For each crop species yield was mainly influenced by rainfall amount and distribution (75–88% yield variation), and tillage × genotype was of little importance. The overall results suggest that a specific breeding program for CA in lentil, chickpea, wheat, and barley may not be efficient. Few tillage × genotype interaction, especially in dry years, indicated that breeding target on increasing HI, tolerance to drought (high yield in dry years), and potential yield (high yield in wet year) can help to improve yield performance of chickpea, lentil, and wheat genotypes in CA system. Varieties with wider adaptability considering drought tolerance, higher yield with stability, and adoption of CA practices are important in the context of the Mediterranean rainfed environment. Integrating trade-off analysis between yield potential and stability in a rainfall gradient in both CT and CA in the national certification scheme of varieties may be more efficient than developing breeding programs for each type of tillage system.